Great leaders grow : becoming a leader for life - Blanchard, Kenneth H.; Miller, Mark, 1959- (San Francisco : Berrett-Koehler Publishers, 2012)
'Successful leaders don't rest on their laurels. Leadership must be a living process, not a title on a business card, and life means growth. As Ken Blanchard and Mark Miller write in the introduction,'the path to increased influence, impact, and leadership effectiveness is paved with personal growth.... Our capacity to grow determines our capacity to lead. It's really that simple.' Great Leaders Grow shows leaders and aspiring leaders precisely which areas to focus on so they can remain effective throughout their lives.As the book opens, Debbie Brewster, an accomplished leader herself, becomes a mentor to Blake, her late mentor's son, as he begins his career. Debbie tells Blake,'How well you and I serve will be determined by the decision to grow or not. Will you be a leader who is always ready to face the next challenge? Or will you be a leader who tries to apply yesterday's solutions to today's problems? The latter will ultimately fail. The difference: the decision to grow. And not a short-term decision but a decision to grow throughout your career and throughout your life. This single decision is a game changer for leaders.'Over the next several weeks Debbie reveals what this means in practical terms. She and Blake explore four ways that leaders must continue to grow, both on the job and off, because who you are as a leader is inextricably connected to who you are as a person. Whether you're a CEO or an entry-level employee, you'll be inspired to reflect on your own life and to design your own unique long-term growth plan, leading to not only continuing professional success but personal fulfillment as well. '--
Keywords: Leadership; Industrial management; Management